2013
DOI: 10.1080/10503307.2012.721938
|View full text |Cite
|
Sign up to set email alerts
|

Irregular assimilation progress: Reasons for setbacks in the context of linguistic therapy of evaluation

Abstract: The assimilation model suggests progress in psychotherapy follows an eight-stage sequence described by the Assimilation of Problematic Experiences Scale (APES). This study sought to reconcile this developmental stage model with the common but superficially contradictory clinical observation that therapeutic advances alternate with setbacks. Setbacks (n=466) were identified in therapy transcripts of two clients and classified using a preliminary nine-category list of possible alternative reasons for setbacks. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 49 publications
2
40
0
7
Order By: Relevance
“…Identification of the main problematic experience. We followed the procedures adopted in previous studies regarding the identification and definition of relevant problematic experiences in psychotherapy (e.g., Brinegar, Salvi, Stiles, & Greenberg, 2006;Caro Gabalda & Stiles, 2013;Honos-Webb, Stiles, & Greenberg, 2003;Stiles, Meshot, Anderson, & Sloan, 1992). This task was conducted by a total of eight judges, one judge had a Ph.D. in clinical psychology, one was a Ph.D. student in clinical psychology and six were Master's students in clinical and health psychology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of the main problematic experience. We followed the procedures adopted in previous studies regarding the identification and definition of relevant problematic experiences in psychotherapy (e.g., Brinegar, Salvi, Stiles, & Greenberg, 2006;Caro Gabalda & Stiles, 2013;Honos-Webb, Stiles, & Greenberg, 2003;Stiles, Meshot, Anderson, & Sloan, 1992). This task was conducted by a total of eight judges, one judge had a Ph.D. in clinical psychology, one was a Ph.D. student in clinical psychology and six were Master's students in clinical and health psychology.…”
Section: Methodsmentioning
confidence: 99%
“…Then the judges worked together to identify excerpts in the transcripts where each problematic experience appeared that were then marked with different colors. Specifically, the excerpts of the problematic experiences were identified from content (what was talked about) (Brinegar et al, 2006;Caro Gabalda & Stiles, 2013). Finally, the main problematic experience was identified through a consensual discussion between the two judges about the clinical relevance of the content.…”
Section: Methodsmentioning
confidence: 99%
“…The Assimilation Model conceptualises how patients progressively integrate their problematic experiences during psychotherapy (Stiles, 2002, 2011). It has been constructed primarily through theory‐building case studies, and further case studies continue to extend, elaborate, and refine it (e.g., Brinegar, Salvi, Stiles, & Greenberg, 2006; Caro Gabalda & Stiles, 2013; Goldsmith, Mosher, Stiles, & Greenberg, 2008; Kramer & Meystre, 2010; Osatuke & Stiles, 2006). The self is seen as made up of different voices , centres of experience, interconnected by the sharing of meaning (Honos‐Webb & Stiles, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The ZPD has also been used to successfully account for setbacks, that is, reversals in therapeutic progress, which had previously seemed to pose a contradiction to the assimilation model's stage theory (Caro Gabalda, ; Detert, Llewelyn, Hardy, Barkham, & Stiles, ). Caro Gabalda and Stiles () suggested that setbacks occur when therapists' interventions exceed clients' current capacity for self‐understanding (i.e., beyond the upper limit of the problem's current ZPD). Faced with such interventions, clients fail to make advances in assimilation or even regress to an earlier stage of assimilation.…”
Section: Introductionmentioning
confidence: 99%